Substrate-Dependent Differences in the Crystal Structures and Optical Properties of ZnSe Nanowires. (13th October 2015) - Seo, Keumyoung; Bong, Jihye; Kim, Jae-Woo; Song, Yoon-Ho; Shin, Yong Ho; Kim, Yongmin; Ju, Sanghyun
Abstract : The optical and structural properties of ZnSe nanowires directly grown on three different substrates, SiO2, ITO, and graphene, were investigated. ZnSe nanowires grown on graphene and SiO2 were found to have cubic structures, while ZnSe nanowires grown on ITO had a mixed cubic and hexagonal structure. The main peaks in the photoluminescence spectra of ZnSe nanowires grown on SiO2, ITO, and graphene were located at 459, 627, and 627/460 nm, respectively. In addition, a field-emission light-emitting device was fabricated using ZnSe nanowires as a phosphor and graphene as an electrode. The device showed a red emission peak with Commission Internationale de L'Eclairage coordinates of (0.621, 0.315).